2017
DOI: 10.22266/ijies2017.0831.07
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Aware Test Suite Minimization Approach Using TAP Measure and Greedy Search Algorithm

Abstract: Software testing is required to detect the faults and to ensure the quality of the software under development. Usually, test suites are used to evaluate the software system during the software development cycle. But often test suites contain more redundant test cases due to overlapped test objectives. So, the test-suite reduction is an important step to reduce the number of test cases so as to satisfy the entire objectives with less computational cost. Literature presents different methods to select the suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In the first approach, the authors devised an ATAP measure TSR based on FPA called TGFP. They evaluated the proposed strategy performance with TBAT [64], greedy ratio [105], greedy EIrreplaceability [65], diversity-based GA [106], and TAP [106] for combinatorial testing. Based on the performed experiments, they reported that TGFP attained better performance in terms of test optimisation than the compared approaches.…”
Section: Swarm Intelligence-basedmentioning
confidence: 99%
“…In the first approach, the authors devised an ATAP measure TSR based on FPA called TGFP. They evaluated the proposed strategy performance with TBAT [64], greedy ratio [105], greedy EIrreplaceability [65], diversity-based GA [106], and TAP [106] for combinatorial testing. Based on the performed experiments, they reported that TGFP attained better performance in terms of test optimisation than the compared approaches.…”
Section: Swarm Intelligence-basedmentioning
confidence: 99%
“…In future, we plan to verify the test suite reduction approaches for fault detection capability. Table 7 W-test on p-value (α = 0.01) and p-value (α = 0.1) DIV-TBAT versus GR [26] DIV-TBAT versus GE [24] DIV-TBAT versus DIV-GA [21] DIV-TBAT versus TAP [21] DIV-TBAT versus TBAT [22] DIV-TBAT versus ATAP DIV-TBAT versus GR [26] DIV-TBAT versus GE [24] DIV-TBAT versus DIV-GA [21] DIV-TBAT versus TAP [21] DIV-TBAT versus TBAT [22] DIV-TBAT versus ATAP…”
Section: Conclusion and Future Scopementioning
confidence: 99%
“…Summarising, the contributions of this paper are: i. New measure: A newly proposed measure called ATAP measure (Adaptive Test cases which is already included in Pool-based measure) which is the extension of the TAP measure given in [21]. ii.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, HGS approach is based on selection of test cases according to their degree of essentialness, i.e., the order of test cases is most essential to least essential in the reduced test suite. On the other hand, Shounak et al [20] proposed an algorithm i.e. GTAP) using TAP (Test cases which Already included in Pool-based Measure) measure and greedy search algorithm to reduce the number of test cases.…”
Section: Introductionmentioning
confidence: 99%